Mucocutaneous Manifestations Among HIV-Infected Patients in Madagascar: Cross-Sectional Study - Fandresena Arilala Sendrasoa; Volatiana Mercia Falimiarintsoa; Lala Soavina Ramarozatovo; Fahafahantsoa Rapelanoro Rabenja (JMIR Publications, 2023)
BackgroundMore than 90% of HIV-infected patients present with at least one mucocutaneous manifestation during the course of their disease. Insufficient data are available regarding dermatologic findings among HIV-infected patients in Madagascar. ObjectiveThis study aimed at evaluating the spectrum of mucocutaneous manifestations and their relationship with CD4 cell counts in HIV-infected patients in Madagascar. MethodsA cross-sectional study on HIV-positive patients attending the Department of Infectious Diseases in the University Hospital of Antananarivo in Madagascar was conducted from January 2013 to March 2020. HIV-positive patients older than 18 years and receiving antiretroviral therapy as well as those awaiting antiretroviral therapy commencement were included. ResultsAmong 328 patients enrolled in this study, 167 (51%) presented with at least one type of mucocutaneous lesion. Oral candidiasis was the most common presentation, followed by seborrheic dermatitis and Kaposi sarcoma. Decreases in CD4 cell counts were substantially correlated with oral candidiasis, syphilis, and condyloma acuminatum. ConclusionsAccording to our findings, oral candidiasis, syphilis, and condyloma acuminatum may serve as clinical indicators for predicting the immune status of patients. As HIV infection progressed and immune function declined, an increase in cutaneous manifestations was observed.